Studi Komparatif Unsur pada Firma dan Syirkah Al-Inan - Rosida Rosida (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2017)
Based on business world has in life time of all person. Know have a two big pattern and brings the own path. Booth og the model is wit syariah scheme and convensional scheme. Booth has a varian product. In this paper more focus on Firm and Shirkah al-Inan. After the analyst with comparison, founded as a same thing and the defference thing. Therefore it begin some discribing, if we seen booth with whole fundamentality.